(untitled) (The Batuk, 2024)
This study was conducted to examine the impact of credit risk and macroeconomic variables on the profitability of commercial banks in Nepal. Return on assets and earnings per share of the banks were taken as regrassands. Whereas, as regressors, non-performing loan, capital adequacy ratio and credit to deposit ratio were taken as the proxies of credit risk, and GDP growth rate, consumer price index and base rate were studied as indicators of macroeconomic variables. Following simple random sampling techniques, 14 commercial banks were selected as sample for the study. The required quantitative data were retrived from annual financial reports of the banks. Data were analyzed on Gretl software. The Pearson correlation and Ordinary Lease Square model for regression resulted that the GDP growth rate was insignificant in defining the variation on return on assets. Likely, inflation and base rate were not significant in defining the variation on earning per share. Result of this study provided sufficient scope to bankers in developing their growth strategies.